ANALISIS KEPATUHAN PAJAK PENGHASILAN DI KALANGAN USAHA KECIL DAN MENENGAH (UKM) - Gladis Jelita; Laila Rahmayuni Rangkuti, Putri Andriani Jambak, Dini Vientary (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to determine and understand the influence of the tax system and tax services on SME taxpayer compliance using qualitative methods. Through a case study approach, this research involved in-depth interviews with 15 SME owners in various sectors. Data were analyzed using the thematic analysis method to identify motives, perceptions and experiences that influence tax compliance. The research results show that understanding and knowledge of taxation as well as an effective and efficient taxation system influence the level of compliance of SME taxpayers. SME taxpayer compliance is influenced by several factors, including taxpayer awareness, education, and good tax services. Knowledge of tax regulations, perception of the tax burden, trust in the government, and experience interacting with tax officials are also factors that can influence compliance. Apart from that, awareness of the benefits of tax for development also motivates several SME owners to comply with tax obligations. This research provides insights that can be used by policy makers to improve education strategies and more effective tax services for SMEs